Bridging yesterday and tomorrow: Responses to the new disability rights paradigm in the post-socialist region - Egl; Gevorgianiene, Violeta; Geniene, Rasa (Disability Studies Quarterly, 2021)
In the post-socialist region, both disability NGOs and disability research have been hostages of the medical model. The last decades mark the end of this dependence, however, a question remains over whether disability activism and research have become allies, implementing human rights-based disability policy. The goal of this paper is to reveal the relationship between academic disability research and disability activism and their influence on disability policy in the post-socialist region. The objectives of the research are to analyze the peculiarities of academic disability discourse and disability activism, their intersection points as well as their actual impact on disability policy. As a reference point for this analysis, we will take the trends of disability discourse and the rise of disability activism in the Global North countries. Thus, this paper contributes to the „careful dialogue" (Rassel, Iarskaia-Smirnova, 2013) between the post-socialist and Western understandings of disability. Authors overview the emergence of civil society and disability activism in post-socialist countries, discuss the changing role of researchers in the disability field, present and compare findings from experts' research, and quantitative content analysis of disability-related academic texts.